PERFORMANCE MANAGEMENT AS A TOOL FOR PERFORMANCE IMPROVEMENT IN THE MANAGEMENT OF BUILT FACILITIES - Edoghogho OGBEIFUN (Journal of Construction Project Management and Innovation)
Effective operation of functional built facilities required for the performance of the core functions of an organization demands the contextual use of the principle of listening to the voice of customers, through performance assessment, leading to performance improvement. Performance improvement is a critical factor necessary for improved productivity and enhanced customer satisfaction. Many approaches have been developed to achieve this, but the most reliable is through sustained commitment to the principle and activities in the performance management loop. In this study the single case study of qualitative research was adopted; data collection and analysis were achieved using the mixed methods approach. The semi-structured  questionnaire complemented with an interview was used to collect the qualitative data and was analysed following the principle of content analysis. The structured questionnaire was used to collect quantitative data from the respondents; analysis of feedback helped in identifying areas of variances, which were discussed in a focus group session before developing performance improvement strategies. The findings revealed that subjecting performance assessment results to further analysis helps to identify the areas of latent discontent, which should be resolved before developing performance improvement strategies. Successful operation of the built facilities available for the execution of the core functions of any organization requires the active collaboration between the unit responsible for the operation and maintenance and those responsible for the execution of the core functions. This synergy is required for sustained performance improvement and customer satisfaction requires commitment to the periodic repetition of the activities in the performance management loop.